Efficacy Analysis of Combinatorial siRNAs against HIV Derived from One Double Hairpin RNA Precursor - Liu, Chang; Liang, Zhipin; Kong, Xiaohong (Frontiers in Microbiology, 2017)
Combinatorial small interfering RNA duplexes (siRNAs) have the potential to be a gene therapy against HIV-1, and some studies have reported that transient combinatorial siRNA expression represses HIV replication, but the effects of long-term siRNA expression on HIV replication have not been studied in detail. In this study, HIV-1 replication under the influence of stable combinatorial siRNA expression from a single RNA transcript was analyzed. First, a series of cassettes encoding short hairpin RNA (shRNA)/long hairpin RNA (lhRNA)/double long hairpins (dlhRNA) was constructed and subjected to an analysis of inhibitory efficacy. Next, an optimized dlhRNA encoding cassette was selected and inserted into lentiviral delivery vector FG12. Transient dlhRNA expression reduced replication of HIV-1 in TZM-bl cells and CD4+ T cells successfully. HIV-1 susceptible TZM-bl cells were transducted with the dlhRNA expressing lentiviral vector and sorted by fluorescence-activated cell sorting to obtain stable dlhRNA expressing cells. The generation of four anti-HIV siRNAs in these dlhRNA expressing cells was verified by stem-loop RT-PCR assay. dlhRNA expression did not activate a nonspecific interferon response. The dlhRNA expressing cells were also challenged with HIV-1 NL4-3, which revealed that stable expression of combinatorial siRNAs repressed HIV-1 replication for 8 days, after which HIV-1 overcame the inhibitory effect of siRNA expression by expressing mutant versions of RNAi targets. The results of this evaluation of the long-term inhibitory effects of combinatorial siRNAs against HIV-1 provide a reference for researchers who utilize combinatorial RNA interference against HIV-1 or other error-prone viruses.